Traveling between the Earth-Moon Lagrangian points and the earth - Oliveira, Geraldo Magela Couto; Prado, Antonio Fernando Bertachini de Almeida; Sanchez, Diogo Merguizo; Gomes, Vivian Martins [UNESP] (My University, 2016)
The idea of the present paper is to study orbital transfers for a spacecraft from the Lagrangian points in the Earth-Moon system to the Earth, as well as to the other Lagrangian points. The model used is the restricted three-body problem with the addition of the effects of the radiation pressure in the trajectory of the spacecraft. The basic maneuver is a bi-impulsive transfers under the dynamics explained before. The results show that the radiation pressure has an influence in the process, although not very large. After that we made some simulations for similar maneuvers in a double asteroid system, where the gravitational forces are smaller and the radiation pressure gives important contributions to the motion of the spacecraft. It is possible to find solutions with smaller fuel consumption when considering the solar radiation pressure, in both cases, but with important reductions in the magnitude of the impulses required for the asteroid system. It is important always to take into account that the idea presented here is not to use the radiation pressure as a control, but just to measure its effects when performing the bi-impulsive transfer.